PENERAPAN METODE MIND MAPPING DALAM MENINGKATKAN KETERAMPILAN MENULIS - Aprilia , Windi; Gloria Wardania Litak; Ismail; Candra, Anita (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aimed to improve students’ writing skills through the application of the mind mapping method in Indonesian language learning. The background of this study was based on students’ difficulties in determining ideas, developing thoughts, constructing sentences, and organizing paragraphs coherently. This research employed Classroom Action Research conducted in two cycles. Each cycle consisted of planning, action, observation, reflection, and re-planning stages. The subjects of this study were 28 fourth-grade elementary school students. The data were collected through observation, writing tests, and documentation. The research instruments included observation sheets, mind mapping worksheets, writing tests, and a writing assessment rubric. The data were analyzed using descriptive quantitative and qualitative analysis. The results showed an improvement in students’ writing skills after the implementation of the mind mapping method. The students’ average score increased from 57.8 in the pre-cycle to 68.4 in cycle I and reached 79.6 in cycle II. The percentage of learning mastery also increased from 32% in the pre-cycle to 64% in cycle I and reached 86% in cycle II. Based on these findings, it can be concluded that the mind mapping method can improve students’ writing skills by helping them organize ideas, develop thoughts, and produce more coherent and well-structured writing.